Th and U isotopes, dose rates and ages of marine shells and sediment of core GIK14350, north Germany, supplementary data to: Hoffmann, Dirk; Woda, Clemens; Lomitschka, Michael; Mangini, Augusto (1999): Untersuchungen zur ESR-Datierung eemzeitlicher Muscheln aus Schleswig-Holstein. Meyniana, 51, 113-124 - Hoffmann, Dirk; Woda, Clemens; Lomitschka, Michael (PANGAEA - Data Publisher for Earth & Environmental Science, 1999)
The ESR dating method was applied to marine shells taken from a sediment core from Dagebüll, Schleswig-Holstein. Four samples from two different depths of the core (17.5 m and 25-26 m), separated by a 2.76 meter thick clay layer (Turritella Clay), yielded identical ages within the limits of error. They indicated an assignment to the oxygen isotope stage 5, thus confirming the stratigraphic age. In addition, the ESR-ages confirm the interpretation of Lomitschka et al. (1997, doi:10.2312/meyniana.1997.49.85), that the Th/U-ages of shells below the clay layer are reliable, whereas shells located above the clay layer, which were strongly influenced by percolating groundwaters of an open system, yielded falsified Th/U-ages.
This dataset is supplement to doi:10.2312/meyniana.1999.51.117
Keywords: Datensammlung